(untitled) (The Conference Hub, 2025)
One of the most significant developments in human history was the invention of writing. A key factor in the emergence of writing was the human capacity for conceptual thinking, as writing — that is, a system of signs — is directly linked to thought processes. Writing typically originates in a specific region and spreads to other regions through cultural contacts.